ZOLTÁN DÖRNYEI’S IMPACT ON LANGUAGE ACQUISITION AND EDUCATION STUDIES: A SCOPUS-BASED BIBLIOMETRIC STUDY (1991-2023) - Syahid, Abdul; Aghayani, Behnam (LLT Journal: A Journal on Language and Language Teaching, 2024)
Previous literature reviews and bibliometric studies have paid much attention to the scientific outputs of Zoltán Dörnyei, a leading figure in the field of second language acquisition and education. However, little attention has been paid to his scholarly impact. This study aims to analyze all publications citing his 87 works in Scopus. Bibliometrix, a comprehensive bibliometric tool, was run to analyze 7,621 documents published in 1,970 sources by 9,226 authors of 2,652 institutions across 99 countries between 1991 and 2023. The analyses include the publication trend, research contributors, including authors, document elements including keywords, collaboration networks of research contributors, shared references, and frequently used keywords. Although most documents were written in English in the fields of social sciences as well as arts and humanities, his impact could be observed across other subject areas and languages. Further discussion elaborated on four major themes of the publications, including motivation, L2 motivational self-system, language learning, and positive psychology. This study could provide researchers and educators with valuable insights into understanding and improving language acquisition processes based on Dörnyei’s incalculable intellectual contribution. As this study focused on quantitative citation analysis, future research on how Dörnyei’s works were cited could provide deeper insights into his impact.